Discovery of Unique Lanthionine Synthetases Reveals New Mechanistic and Evolutionary Insights - Goto, Yuki; Li, Bo; Claesen, Jan; Shi, Yanxiang; Bibb, Mervyn J.; van der Donk, Wilfred A. (PLOS Biology, 2010)
Identification of a new class of lanthionine synthetases provides insight into the mechanism and evolution of cyclic peptide biosynthesis.